Pendidikan Humanistik Dalam Perspektif Al-Qur’an - Muhtadi, Mohammad (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2021)
The concept of humanistic education in the Qur'an contains elements including: a) Human education physically and biologically; b) inner human education and psychology; c) social human education and d) spiritual education. Concepts in the perspective of Al-Qur’an which become the foundation for a humanist education, including: the nature of human form, the potential of humanity, and the purpose of human creation. The humanization applied in the Qur'an does not leave the role of man on earth as its function and role as